PREDICTION AND AUTOMATION OF AGRICULTURAL PRACTICES FOR PADDY CULTIVATION USING AMBIENT INTELLIGENCE - C, Angel (Institute of Advanced Engineering and Science, 2020)
Many researchers focused on automating the activities performed in agriculture using technology. These will certainly a good move towards smart precision agriculture. Integrating intelligent technology using ambient intelligence can create a more visualized interactive and responsive environment. Several existing methods focused on providing automatic irrigation, identification of diseases and prediction crop yield using IoT and image processing. However automating all these activities for a particular cultivation is not an easy task. In this paper, a new intelligent system (IntPaddy) is proposed for automating the cultivation of paddy using ambient in9telligence. This provides farmer an ambient assisted environment for managing their cultural practices. Result also shows that the system will keep on learning and updating based on the farmer?s preferences and activities, thereby enabling them to focus more on other activities also.